Biochemical Abnormalities Associated with High Dose Methotrexate (HDMTX) Toxicities in Children with ALL and NHL - Kabir, Ahsan; Azad, Farzana Azma; Moniruzzaman, S M; Khan, Mohammad Farid; Kundu, Tarak Nath; Islam, Afiqul (The Planet, 2023)
Introduction: Childhood leukemia and lymphoma are twocommon malignancies that cause morbidity and mortality.Acute lymphoblastic leukemia (ALL) is the most prevalenttype, while non-Hodgkin lymphoma (NHL) is the thirdmost common. Treatment for these malignancies oftenincludes high-dose methotrexate (HD-MTX), which cancause significant toxicity. MTHFR gene polymorphismshave been linked to increased toxicity. This study aims todocument the biochemical abnormalities associated withHDMTX toxicity in children. Methods & Materials: Thisstudy was conducted prospectively in the Department ofPediatric Hematology & Oncology at BSMMU in Dhakabetween July 2015 and December 2015. The studypopulation included children under the age of 15 who werediagnosed with Acute Lymphoblastic Leukemia (ALL) orNon-Hodgkin Lymphoma (NHL) and were receiving high-dose methotrexate (HDMTX) aspart of their treatment. Results: The study population consisted of 30 patients with childhoodmalignancy, with Acute Lymphoblastic Leukemia (ALL), being the most common malignancy76.7% followed by non-Hodgkin lymphoma 23.3%. Biochemical toxicities such as elevatedtransaminases and raised creatinine were observed in 6.7% and 3.3% of patients,respectively, but no neurotoxicity was reported. Hematological toxicities such as neutropenia and thrombocytopenia were observed in 26.7% and 3.3% of patients, respectively, with ahigher occurrence in cycles 2 and 3 compared to cycle 1.Hematological recovery occurredby day 12 in most cases. Conclusion: This study found that elevated transaminases andraised creatinine were the major biochemical toxicities associated with HDMTX infusion,while neutropenia and thrombocytopenia were the major hematological toxicities observed.